The rise and fall of olympic amateurism - Llewellyn, Matthew P.; Gleaves, John (Sport and society., 2016)
"No sporting event is more culturally significant and popular than the Olympic Games. An estimated 4 billion people watched the opening ceremonies for the 2012 London Games. The Olympic logo of five interlocked rings outpaces both Nike and McDonalds for positive global recognition. The Olympic Games have embraced values such as character, fair play, chivalry, internationalism, and peace. Historically, these values emerged as part of the International Olympic Committee's policy of amateurism. Although there have been several works exploring smaller facets of the Olympic Games, there has never been a definitive book, grounded in historical research, exploring Olympic amateurism, the Games' most enduring ideal. This book represents a comprehensive exploration of the historical development and eventual decline of amateurism within the modern Olympic Games. At its inception, the International Olympic Committee required that all Olympic athletes comply with amateur rules that prohibiting them from profiting in any capacity from their sporting participation. However, over the course of the twentieth century, these rules first grew more rigid before gradually relaxing and dissolving. By the close of the millennium, the vast majority of Olympic athletes were openly professionals, with salaries and private endorsements. An Enduring Ideal: The Rise and Fall of Olympic Amateurism presents the first major history that explores how changes to the culture of sport coupled with shifting political forces brought about the eventual end to the century's most enduring sporting ideal"--